Evaluating the influences of connection forms on the cyclic performance of RSFBs. Issue 143 (April 2021) - Jiang, Qing; Wang, Hanqin; Feng, Yulong; Chong, Xun
Abstract: A rocking steel frame with buckling-restrained braces (RSFB) with excellent deformation controlling and energy dissipating capacities is proposed to retrofit conventional steel frames. Notably, previous studies have shown that the seismic performance of structures with buckling-restrained braces (BRBs) was influenced by the connection forms of the BRBs within the structures. In this study, a series of pseudostatic tests were conducted on the RSFBs to investigate the influence of the BRB and support connection forms on the structural seismic performance. An out-of-plane deformation is observed in the transiting portion of the compressional BRB because of the failure of the out-of-plane restraints. However, the BRB on the tensional side works normally, and the RSFBs do not fully lose their carrying capacity. The rocking steel frames in all test specimens remain elastic and demonstrate uniform inter-story drifts. Finite element models of the test specimens with full out-of-plane restraints were established and simulated using ABAQUS software to complement the tests. The simulation results show that the BRB and support connection forms have little influence on the overall structural hysteresis response. However, the BRB connection forms affect the deformation of the BRB core plate and the out-of-plane deformation at the BRB ends due to different out-of-plane stiffnesses. Moreover, the supports with various connection forms exhibit different damage degrees and distributions. Highlights: The influences of connection forms on the cyclic performance of RSFB and deformation of support and BRB through pseudostatic tests and numerical simulation. The changes in the BRB and support connection forms have little influence on the overall structural cyclic performance; however, these changes have larger influences on the BRB and support deformation and failure modes. Enhancing the out-of-plane stiffness in the column-BRB joint generates a uniform deformation in the energy dissipating portion of the BRB core plate.